ANALISIS STRATEGI PENGEMBANGAN DENGAN ANALISIS SWOT SEBAGAI KAWASAN WISATA UNGGULAN DAERAH (Studi Kasus Kawasan Wisata Jumiang Kabupaten Pamekasan) - Yuyun Sasmita; Campina Illa Prihantini; Nursalam Nursalam; Musoffan Musoffan; Darwis Darwis (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Jumiang tourist area is a one of the top tourist attraction in Pamekasan Regency, East Java. This area consists of beaches and hills that have a distinctive natural beauty. The research analyses the development strategy of of Jumiang tourist area as a nautical tourism in the future. The analysis is conducted with a qualitative method of analysis, namely SWOT analysis. The results of the analysis showed that the development of the tourist area Jumiang can utilize various ways in accordance with the results of the SWOT analysis that has been described in this study. Hopefully, the results of this study and research can be the basis and consideration materials in the development of sustainable education tourism (sustainable edutourism) in Pamekasan District, so that the community can be more independent in economic life.